The Influence Of Leadership Style, Work Environment, And Compensation On Employee Loyalty - Sekar Laras Ati; Akhmad Darmawan; Hengky Widhiandono; Wida Purwidianti (Jurnal Mantik, 2024)
This study examines the effect of Leadership Style, Work Environment, and Compensation on Employee Loyalty at Java Heritage Hotel Purwokerto. The study used purposive sampling with a total sample of 107 from a population of 135 in 2023. The data used in this study is primary data obtained by distributing questionnaires and processed with SmartPLS software using data analysis techniques, an outer model for validity and reliability tests, an inner model for R-square tests, and hypothesis testing using structural equation models. The results showed that Leadership Style had a positive and significant effect on Loyalty, Work Environment had a negative and significant impact on Loyalty, and Compensation had a positive and significant effect on Loyalty